Analisis Digital Marketing, Quality Product Dan Brand Image Terhadap Keputusan Pembelian Konsumen Pada Matahari Brand Trenggalek Saat Pandemi Covid – 19 - Trisna Trihapsari; Abu Talkah (Universitas Islam Kadiri, 2022)
This study aims to examine the relationship between digital marketing, product quality and brand image on consumer purchasing decisions at Matahari Brand Trenggalek during the covid-19 pandemic. This study uses secondary data with a sample of 102 respondents. Analysis of the data used is by using SPSS. This type of research is quantitative research by distributing questionnaires through google form to Matahari Brand Trenggalek consumers.The sampling technique used was purposive sampling and 102 samples were obtained from 137 Matahari Brand Trenggalek consumers. This study uses multiple linear regression. The results show that digital marketing has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on purchasing decisions and brand image has a negative and insignificant effect on purchasing decisions